2022
DOI: 10.1002/jev2.12178
|View full text |Cite
|
Sign up to set email alerts
|

Biodistribution of unmodified cardiosphere‐derived cell extracellular vesicles using single RNA tracing

Abstract: Extracellular vesicles (EVs) are potent signalling mediators. Although interest in EV translation is ever‐increasing, development efforts are hampered by the inability to reliably assess the uptake of EVs and their RNA cargo. Here, we establish a novel qPCR‐based method for the detection of unmodified EVS using an RNA Tracer (DUST). In this proof‐of‐concept study we use a human‐specific Y RNA‐derived small RNA (YsRNA) we dub “NT4” that is enriched in cardiosphere‐derived cell small EVs (CDC‐sEVs). The assay is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…Our findings demonstrate that CPC-EVs co-localize with cardiomyocytes and endothelial cells after administration in the left ventricle wall, suggesting their interaction with these cell types. This is in accordance with previous observations of CPC-EV uptake by cardiac cells in the ischemic left ventricle (Maring et al, 2019), and internalization in cardiomyocytes (Chen et al, 2013;Barile et al, 2018;Ciullo et al, 2019), endothelial cells (Youn et al, 2019), macrophages and cardiac fibroblasts (Ciullo et al, 2022) in vitro. EVs can activate recipient cells not only after their uptake and subsequent release of bioactive cargo, but also through direct EV-cell interactions for which no internalization is required (Roefs et al, 2020;van Niel et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…Our findings demonstrate that CPC-EVs co-localize with cardiomyocytes and endothelial cells after administration in the left ventricle wall, suggesting their interaction with these cell types. This is in accordance with previous observations of CPC-EV uptake by cardiac cells in the ischemic left ventricle (Maring et al, 2019), and internalization in cardiomyocytes (Chen et al, 2013;Barile et al, 2018;Ciullo et al, 2019), endothelial cells (Youn et al, 2019), macrophages and cardiac fibroblasts (Ciullo et al, 2022) in vitro. EVs can activate recipient cells not only after their uptake and subsequent release of bioactive cargo, but also through direct EV-cell interactions for which no internalization is required (Roefs et al, 2020;van Niel et al, 2022).…”
Section: Discussionsupporting
confidence: 93%
“…These findings support the potential use of CDC‐derived exosomes as a promising therapeutic strategy for MI 90 . Furthermore, studies have shown that intravenous CDC‐EVs accumulate primarily in the heart and that cardiac injury enhances the uptake of CDC‐EVs by the heart, liver, and brain 91 . Additional studies have proposed that CDCs might be more efficacious than MSCs in MI models.…”
Section: Evs Derived From Different Cell Types Promote the Treatment ...supporting
confidence: 57%
“…Studies have shown that EVs from heart‐related cells are rapidly absorbed by heart tissue, and there is evidence that cells preferentially take up EVs from the same tissues 197 . Besides myocardial cells, macrophages, ECs, and fibroblasts are the primary recipients of EVs, and these cell types may mediate the cardioprotective effect 91 . These heart‐related cell‐derived EVs may play an important role in treating CVDs.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac cell-derived EVs encapsulate many miRNAs like miR-146a, miR-181b, and miR-26a, and have exhibited improved cardio-protective and therapeutic effects than MSC EVs under MI conditions [ 99 , 100 , 101 , 102 ]. Using single RNA tracing, cardiac endothelial cells and cardiac fibroblasts have shown increased intake of cardiosphere cell-derived EVs following injury [ 103 ]. Several cardiomyocyte EC-derived miRNAs such as miR-23a-3p, miR-424, let-7f, miR-378, and miR-214 might be one of the crucial cardio protecting factors [ 104 ].…”
Section: Ex-ncrnas As Therapeutic Targets In Cvdsmentioning
confidence: 99%